Keunggulan Khotbah Expository - Chornalius Blegur; Ayub Sugiharto (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
Expository preaching is a type of preaching that is considered to promote the validation and inerrancy of the Bible. In accordance with the doctrine of inerrancy in the Bible, it explains the texts of the Truth of the past and this should also be applied to the partners in the 21st century. This means that biblical texts that claimed to be true in the past are still relevant today. To bring it to the present, the meaning and intent of the biblical text must first be understood by the expositor. Therefore, this research tries to explore some writings about the advantages of expository preaching, namely. 1. Helping the congregation understand the intent and purpose of God's Word. 2. Ensuring an accurate and comprehensive understanding of the Bible. 3.Encouraging spiritual growth. 4. Helps the congregation apply the teachings of the Bible to their daily lives. 5. Provide variety to maintain the interest of the congregation. Through this article the author will discuss how many things are related to the advantages of expository preaching, namely 1. What is expository preaching? 2. What are the advantages of expository preaching? 3. What are the steps in preparing an expository sermon? In the steps of preparing an expository sermon, it involves exegesis in the form of in-depth research on the verses to be preached, the use of various research aids such as Bible commentaries, lexicons, Bible dictionaries, encyclopedias, and other books related to preparing expository sermons. Next, the results of the study can be compiled into an expository sermon. The next step is the task of hermeneutics, adapting it to the current needs of the congregation. The final step is how the preacher then uses the art of rhetoric with various communication skills to be able to convey the Biblical message according to the audience and their current needs. The entire process is aimed at delivering a sermon that is biblical yet current.